2015
DOI: 10.17305/bjbms.2016.683
|View full text |Cite
|
Sign up to set email alerts
|

G-protein-coupled estrogen receptor-30 gene polymorphisms are associated with uterine leiomyoma risk

Abstract: The G-protein-coupled estrogen receptor , GPER-1) is a member of the G-protein-coupled receptor 1 family and is expressed significantly in uterine leiomyomas. To understand the relationship between GPR30 single nucleotide polymorphisms and the risk of leiomyoma, we measured the follicle-stimulating hormone (FSH) and estradiol (E2) levels of 78 perimenopausal healthy women and 111 perimenopausal women with leiomyomas. The participants' leiomyoma number and volume were recorded. DNA was extracted from whole bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The observed differences in UF risk may be related to the occurrence of other currently not clearly identified specific genetic variants. The effect of rs934099 in ESRα gene [24] as well as [51] rs3808351 polymorphism in the gene coding G-protein-coupled oestrogen receptor (GPR30), a member of the G-protein-coupled receptor 1 family, was recently proven to be associated with UF risk occurrence and a number of tumours [51]. However, more data are necessary to assess the role of these genetic variants in UF development.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences in UF risk may be related to the occurrence of other currently not clearly identified specific genetic variants. The effect of rs934099 in ESRα gene [24] as well as [51] rs3808351 polymorphism in the gene coding G-protein-coupled oestrogen receptor (GPR30), a member of the G-protein-coupled receptor 1 family, was recently proven to be associated with UF risk occurrence and a number of tumours [51]. However, more data are necessary to assess the role of these genetic variants in UF development.…”
Section: Discussionmentioning
confidence: 99%
“…Applying "reverse translational medicine" we should rethink our therapeutic approaches when using these drugs which also suggest possible new therapeutic indications such as for the treatment of bleeding in hereditary heamorrhagic telangiectasia [182] and possibilities for future drug development. Medical genetics studies have found that genetic polymorphisms of GPER are associated with changes in cell function [183] or disease susceptibility for dyslipidemia [73], arterial hypertension [108], seminoma [184], gastric cancer [185], breast cancer [186], leiomyoma [187] and gynecomastia in adolescents [188] providing us with new opportunities for personalized medicine, theranostics, and thereby improving treatment and prevention. Continued clinical research is required to increase our understanding of estrogen receptors and the clinically approved drugs targeting them and how these drugs mediate therapeutic benefits and unwanted side effects in patients, which ultimately will improve patient safety and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Given their most recent discovery relative to ERα and ERβ, CVD-related GPER polymorphisms have not been thoroughly investigated although associations were already demonstrated to idiopathic scoliosis [ 155 ], the risk for seminoma [ 156 ] and uterine leiomyoma [ 157 ] and more recently, with risk and development of hypertension [ 158 ]. Moreover, a hypofunctional GPER variant P16L has recently been identified and associated with increased LDL-C in plasma, which may pose an additional risk of atherosclerosis [ 93 ].…”
Section: Genetic Factors Related To Estrogen Receptors and MImentioning
confidence: 99%